PEMBELAJARAN PERKALIAN MENGGUNAKAN DESAIN PMRI BERBANTU MEDIA PAPAN PERKALIAN DI SD NEGERI 4 DERSALAM - Adistiya, Meilinda Dyah; Puspita, Melani Dyah; Zuliana, Eka (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2025)
This study aims to apply a learning design based on Indonesian Realistic Mathematics Teaching (PMRI) to help students learn multiplication material more concretely and meaningfully using multiplication tables. The data source for this study was students in grade 3 of Elementary School 4 Dersalam. This study uses a qualitative descriptive research method. Qualitative research methods emphasize aspects of in-depth understanding of a problem or question rather than looking at a problem to be generalized. Descriptive research is a research method in which people see events and things in their lives and ask someone or a group of people to tell their life stories. The results of the study showed that after using the PMRI learning model, students felt interested in learning and understanding mathematics learning, their mathematical knowledge increased, and students' learning activities also increased. During the learning process, for example, students dare to interact with each other and the teacher.